The phase space of 2+1 Ads gravity - Scarinci, Carlos (2012)
We describe what can be called the “universal” phase space of 2+1 AdS gravity, in which the moduli spaces of globally hyperbolic AdS spacetimes with compact Cauchy surface, as well as the moduli spaces of multi black hole spacetimes are realized as submanifolds. Importantly our phase space also includes all Brown-Henneaux excitations on the conformal boundary of asymptotically AdS spacetimes, with Diff+(S1)/SL(2,R)xDiff+(S1)/SL(2,R) contained as a submanifold.